2011 IEEE Power and Energy Society General Meeting 2011
DOI: 10.1109/pes.2011.6039188
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of Stochastic Differential Algebraic Equations for power system transient stability with random loads

Abstract: This paper summarizes numerical methods for Stochastic Differential Algebraic Equations (SDAEs) with which power system are modeled. The loads are modeled as random variables which appear in algebraic equations. The properties of numerical methods for Differential Algebraic Equations (DAE) and Stochastic Differential Equations (SDE) are reviewed and the first-order backward euler method is proposed for SDAE in power system transient stability simulation. Illustration examples are given on a single-machine-infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 20 publications
(24 reference statements)
0
22
0
Order By: Relevance
“…Their use in power system analysis, however, has thus far been limited. Recent studies have demonstrated the suitability of stochastic calculus for power system analysis, e.g., [5], [6] and [7]. However, the models proposed in these references are not based on real-world measurements and data.…”
Section: A Review Of Stochastic Load Modelingmentioning
confidence: 99%
“…Their use in power system analysis, however, has thus far been limited. Recent studies have demonstrated the suitability of stochastic calculus for power system analysis, e.g., [5], [6] and [7]. However, the models proposed in these references are not based on real-world measurements and data.…”
Section: A Review Of Stochastic Load Modelingmentioning
confidence: 99%
“…B u,i = hB u,i , and B ω,i = hB ω,i . In addition, since the electrical system is subject to various sources of uncertainties including for example frequency measurement uncertainties [17], renewable generation uncertainties [18], and transmission line noise [19], a noise term is added to the discretised equation (8) to give,…”
Section: Mathematical Model Of Multi-area Powermentioning
confidence: 99%
“…and H represnts the control horizon. Also, note that sincex i k enters control area i as external signal, its corresponding ideal pdf is taken to be equal to its actual pdf given in Equation (18). Following the same procedure in [21] the minimum cost function resulting from the minimisation of Equation (16) with respect to the randomised controller c(u i k−1 z i k−1 ) can then be shown to be given by the following recurrence equation,…”
Section: A Randomised Controller Designmentioning
confidence: 99%
“…The second stage consists in associating SDE to the residuals of the Fourier adjustment, which os the Ornstein-Uhlenbeck process. In general, SDE can be used to simulate the continuous behavior of a variable, which is why in engineering topics it is common to find applications to power systems for short-term studies and real time studies [25][26][27], such as the case of small signal stability [28]. However, as an application to the wave generation area, it is not a highly exploited resource [29].…”
Section: Numerical Modelmentioning
confidence: 99%